THE INFLUENCE OF SELF-EFFICACY AND PEER CONFORMITY ON ACADEMIC PROCRASTINATION AMONG STUDENTS AT PRIVATE VOCATIONAL HIGH SCHOOL IN NGANJUK - Eko Hardi Ansyah; Ananda Indria Yulianti (P3I UMSurabaya, 2024)
This study investigates the impact of self-efficacy and peer conformity on academic procrastination among students at private Vocational High School (SMK) in Nganjuk using an inferential quantitative approach with multiple regression analysis. From a total of 857 students, a sample of 247 was selected through random sampling. The instruments used were a self-efficacy scale (α = 0.830), a peer conformity scale (α = 0.825), and an academic procrastination scale (α = 0.826). Data analysis was conducted using IBM SPSS 22 For Windows. The results indicate that self-efficacy has a significant positive effect on procrastination, while peer conformity has a significant negative effect. Together, these variables account for 27.1% of the variance in academic procrastination, with the remaining 72.9% influenced by other factors. The hypothesis is accepted, confirming the influence of self-efficacy and peer conformity on academic procrastination among students at private Vocational High School (SMK) in Nganjuk.